ANALISIS PENGARUH TINGKAT PENGANGGURAN TERBUKA, INDEKS PEMBANGUNAN MANUSIA, DAN UPAH MINIMUM TERHADAP JUMLAH PENDUDUK MISKIN DI INDONESIA TAHUN 2011-2015 - Shinta Setya Ningrum (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2017)
Poverty continues to be a major problem of the world, especially in developing Indonesia. The study has the objective of testing and analyzing Open Unemployment Rate, Human Development Index, and Minimum Wage for Poor People in Indonesia Year 2011-2015. This type of data uses secondary data obtained from Indonesian BPS and also the journal as research support. This research uses panel data model and use eviews9. The regression result shows that the value of Adjusted R-Square is 0.993546 which means 99.35 percent of the variation of the poor population (Y) can be explained by the independent variables in the statistical models that TPT, IPM, and minimum wage. While 0.65 percent of the variation in the number of poor people (Y) is explained by factors outside the model.